Concern about the spread of the invader seaweed Caulerpa taxifolia var. distichophylla (Chlorophyta: Caulerpales) towards the West Mediterranean - MUSCO, L.; ANDALORO, F.; MIKAC, B.; MIRTO, S.; VEGA FERNADEZ, T.; BADALAMENTI, F. (Mediterranean Marine Science, 2014)
<!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: IT; mso-bidi-language: AR-SA;" lang="EN-GB"> The new Australian alien seaweed Caulerpa taxifolia var. distichophylla, after being established along the Turkish Mediterranean coast in 2006, was recorded in Southern Sicily in 2007. Since then local fishermen claimed support to counteract the effects of entanglement of large amounts of the alien strain wrack in their trammel nets, causing the gear to become ineffective. The further northward and westward spread of the new alien strain is supposed to be limited by winter temperature. We present novel data confirming that the new alien strain is fully naturalized in Central Mediterranean and is expanding its range beyond such limit (i.e. the 15°C February isotherm), thus becoming potentially able to colonize the western basin. By means of a preliminary estimation of effects on native polychaete assemblages, and considering some peculiarities of Sicily (mostly linked to its geographical position in the Mediterranean Sea), the risk linked to the increasing range of distribution of the invasive algae is highlighted. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>